Chemisorption of phosphoric acid and surface characterization of As passivated AlN powder against hydrolysis - Ganesh, Ibram (Langmuir : the ACS journal of surfaces and colloids, 2008)
By simply refluxing a commercial AlN powder in a mixture solution of ethanol, H(3)PO(4), and Al(H(2)PO(4))(3) for 24 h at 80 degrees C, the powder was successfully passivated against hydrolysis. The phosphate layer formed on the surface of AlN powder was found to be quite stable toward protecting the powder from hydrolysis. The efficacy of the coating was established by suspending the treated and the untreated powders in water for 72 h and subsequently characterizing them by X-ray diffraction (XRD), Fourier transform infrared (FT-IR), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), and Raman analysis. The good dispersing behavior of the treated AlN powder in water was confirmed by the low viscosity of an AlN suspension containing 50 vol % solids demonstrating the viability of replacing organic solvents by water in colloidal processing of AlN-based ceramics